Modal Analysis Of Carbon/Epoxy Plate By Varying Fibre Orientation - et. al., Venkata Sushma Chinta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Composite laminated plates are widely used in the field of aerospace and navy for some advantages such as higher ratio of stiffness and strength to weight. A variety of laminated plate theories have been developed and applied to engineering practice. Mode shapes do describe the configurations into which a structure will naturally get displaced. Typically, lateral displacement patterns are of primary interest. Based on the load carrying capacity, Structures cannot be regarded safe but should be safe considering the structural dynamic aspects as well. Modal analysis is used to find the offending frequencies and eliminate them by varying the stiffness or mass to ensure the structure is safe from the natural frequency problems.In this paper modal analysis of a SS rectangular plate made of carbon epoxy is carried out using FEA and the results are compared with analytical solution.The fibre angle is changed systematically to see the effect of fibre orientation on natural frequencies and the corresponding mode shapes. The first six natural frequencies and mode shapes of composite laminated plate are obtained. Presented results showed that the properly chosen fibre angle contribute to better dynamic performance, which provides greater flexibility in designing composite structures to suit the engineering need.